Fresno County Bar Association Law Day Luncheon with Robert McConnell - Watkins, Howard::::::::: (1984)
Robert McConnell speaking at lectern; seated at head table: ?, Supervisor Sharon Levy,?, (speaker), Judge Brad Hill and Stan Cardenas Main ballroom of The Fresno Hilton Hotel